1998
DOI: 10.1016/s0092-8674(00)81227-1
|View full text |Cite
|
Sign up to set email alerts
|

SUR-8, a Conserved Ras-Binding Protein with Leucine-Rich Repeats, Positively Regulates Ras-Mediated Signaling in C. elegans

Abstract: We describe the identification and characterization of a novel gene, sur-8, that positively regulates Ras-mediated signal transduction during C. elegans vulval development. Reduction of sur-8 function suppresses an activated ras mutation and dramatically enhances phenotypes of mpk-1 MAP kinase and ksr-1 mutations, while increase of sur-8 dosage enhances an activated ras mutation. sur-8 appears to act downstream of or in parallel to ras but upstream of raf. sur-8 encodes a conserved protein that is composed pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
202
0
3

Year Published

2001
2001
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 195 publications
(212 citation statements)
references
References 43 publications
7
202
0
3
Order By: Relevance
“…NPCs retain stem cell characteristics, including a high proliferative potential and the ability to selfrenew [30]. In this study, we identified Sur8, the scaffold protein of the Ras-ERK pathway [6][7][8], as a factor that maintains self-renewal capacity and the undifferentiated state in NPCs. We indicate that Sur8 is an intracellular biomarker for Nestinpositive undifferentiated NPCs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…NPCs retain stem cell characteristics, including a high proliferative potential and the ability to selfrenew [30]. In this study, we identified Sur8, the scaffold protein of the Ras-ERK pathway [6][7][8], as a factor that maintains self-renewal capacity and the undifferentiated state in NPCs. We indicate that Sur8 is an intracellular biomarker for Nestinpositive undifferentiated NPCs.…”
Section: Discussionmentioning
confidence: 99%
“…The Scaffold proteins such as Sur8, KSR, and MP1 assemble intracellular signaling complexes and can play important roles in cellular responses [3,[46][47][48]. The scaffold proteins can regulate the efficiency of the signaling response by virtue of their ability to form different complexes with the signaling members of the Ras-ERK pathway such as Ras, Raf [7,49], Erbin, and PP1 [6,49]. Concentration of the scaffold proteins influences differential formation of the complexes, resulted in the output of different physiologies [50].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pour ce qui est des deux homologues de HYP chez les mammifères, SAMD10 (SAM domain containing 10) et SAMD12, aucune étude n'est actuellement disponible à leur sujet. Avec KSR et CNK, une autre protéine d'échafaudage, SUR-8, a été détectée chez C. elegans [33,34]. L'homologue humain de SUR-8 aurait la capacité d'associer RAS et RAF [35].…”
Section: Apport Des Modèles Génétiquesunclassified